Comparison of thermophilic and hyperthermophilic dark fermentation with subsequent mesophilic methanogenesis in expanded granular sludge bed reactors. (18th August 2021) - Weide, Tobias; Peitzmeier, Jens; Wetter, Christof; Wichern, Marc; Brügging, Elmar
Abstract: Herein, dark fermentation (DF, V = 5.5 L) and subsequent mesophilic methanogenesis (V = 43.5 L) are run as expanded granular sludge bed reactors (EGSB) at thermophilic (υDF = 60 °C) and hyperthermophilic (υDF = 80 °C) temperatures. A synthetic glucose wastewater is run with a 22.5 g/L chemical oxygen demand (COD) and 48–9 h hydraulic retention times (HRTs), giving organic loading rates (OLRs) of 11–60 g COD/L/d for DF. The maximum hydrogen production rate (HPR) is HPR = 3.0 m³/m³/d for HRT = 9 h with a 50 L/kg COD hydrogen yield (HY) and 40 vol% H2 . Methane production rate (MPR) reaches MPR = 2.6 m³/m³/d with 70 vol% CH4 at HRT = 2.8 d. The highest H2 yields are HY = 180 L/kg COD with 53 vol% H2 (thermophilic, HRT = 48 h). Hyperthermophilic temperatures led to lower HPRs (0.7 m³/m³/d) and MPRs (1.6 m³/m³/d). 53% of Thermoanaerobacterium thermosaccharolyticum as an H2 producer are found. Discoloration of granular sludge from black to white and granule stability was observed in DF. Graphical abstract: Image 1 Highlights: Discoloration of granular sludge from black to white was observed. Granular sludge stability was proven for DF, even at hyperthermophilic conditions. Lactate pathway was dominant for hyperthermophilic dark fermentation. 53% accumulation of Thermoanaerobacterium thermosaccharolyticum (thermophilic DF). Methanogenesis had at least 75% of the total energy share.